Influencia de la perspectiva de sistemas en equipos multidisciplinarios: de la interpretación de la necesidad a la propuesta de solución - Echevarría Gómez, Percy Eduardo (2022)
This document details how my professional career has validated the fulfillment of the Systems Engineering career’s educational objectives I studied between 1996 and 2001. It describes how, despite not having dedicated myself exclusively to any of the most important career's branches - such as networking or software development - the knowledge acquired and professional training allowed me to participate in multidisciplinary projects, and propose, from a systems perspective, solutions for a variety of problems, multifaceted and that implied understanding, not only technical, but management. Likewise, the fundamental role that the systems professional fulfills by serving as a “translator” of the functional requirements of users and what is reflected in technological solutions is evidenced. Towards the end of the report, lessons learned and recommendations are identified that could serve as a baseline for the professional development of future graduates.